Novel wide-bandgap non-fullerene acceptors for efficient tandem organic solar cells - Firdaus, Yuliar; He, Qiao; Lin, Yuanbao; Nugroho, Ferry Anggoro Ardy; Le Corre, Vincent Marc; Yengel, Emre; Balawi, Ahmed H; Seitkhan, Akmaral; Laquai, Frederic; Langhammer, Christoph; Liu, Feng; Heeney, Martin; et al. (Journal of Materials Chemistry A, 2020)
The power conversion efficiency (PCE) of tandem organic photovoltaics (OPVs) is currently limited by the lack of suitable wide-bandgap materials for the front-cell. Here, two new acceptor molecules, namely IDTA and IDTTA, with optical bandgaps (Eoptg) of 1.90 and 1.75 eV, respectively, are synthesized and studied for application in OPVs. When PBDB-T is used as the donor polymer, single-junction cells with PCE of 7.4%, for IDTA, and 10.8%, for IDTTA, are demonstrated. The latter value is the highest PCE reported to date for wide-bandgap (Eoptg >= 1.7 eV) bulk-heterojunction OPV cells. The higher carrier mobility in IDTTA-based cells leads to improved charge extraction and higher fill-factor than IDTA-based devices. Moreover, IDTTA-based OPVs show significantly improved shelf-lifetime and thermal stability, both critical for any practical applications. With the aid of optical-electrical device modelling, we combined PBDB-T:IDTTA, as the front-cell, with PTB7-Th:IEICO-4F, as the back-cell, to realize tandem OPVs with open circuit voltage of 1.66 V, short circuit current of 13.6 mA cm(-2) and a PCE of 15%; in excellent agreement with our theoretical predictions. The work highlights IDTTA as a promising wide-bandgap acceptor for high-performance tandem OPVs.